Signatures of citizenship : petitioning, antislavery, and women's political identity - Zaeske, Susan (Gender & American culture., 2003)
This history analyzes women's antislavery petitions, the speeches calling women to petition and public reaction from 1831 to 1865. It argues that petitioning not only made significant steps to abolish slavery but also contributed toward transforming women's political identity.